PERILAKU KONSUMTIF BELANJA KULINER MELALUI ONLINE PADA MAHASISWA BARU FAKULTAS PERTANIAN UNIVERSITAS UDAYANA TAHUN 2022 - Pratiwi, Putri Reditya; Arisena, Gede Mekse Korri (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the characteristics, analyze consumptive behavior and habits of using online motorcycle taxis in culinary shopping for new students of the Faculty of Agriculture, Udayana University in 2022 and their relationships, and examine culinary business opportunities in the agribusiness sector. The research sample consisted of 81 students using the snowball sampling technique. The data analysis used is descriptive qualitative, descriptive quantitative, and Pearson's Product Moment Correlation. The results showed that: (1) Characteristics of students who shop for culinary goods through online motorcycle taxis: Most are 18 years old, the majority are women, most are Agribusiness students, have pocket money between IDR 600,000 – IDR 1,000,000, the amount additional income is mostly IDR 0, a source of income comes from parents. The type of online motorcycle taxi application that is often used is Gojek (Go-Food). Culinary through online motorcycle taxis shows quite consumptive behavior (3) Students are accustomed to using online motorcycle taxi applications in culinary shopping (4) There is a significant relationship between student consumptive behavior and the habit of using online motorcycle taxi applications in culinary shopping with a moderate level of relationship (5) Business Organic noodles can be used as a culinary business opportunity in the agribusiness sector.